EVALUASI KINERJA MANAJEMEN SUMBER DAYA MANUSIA STARTUP RAWRAMIE DENGAN HUMAN RESOURCE SCORECARD - Freddy Suryadi; Solehudin Solehudin; Nunung Nurhasanah (Universitas Bina Taruna Gorontalo, 2024)
This study aims to evaluate the performance of human resource management at Rawramie Startup as one of the startups in the city of Bandung using the Human Resource Scorecard (HR Scorecard) approach. HR Scorecard was chosen because of its ability to connect Human Resource Management (HRM) activities with the company's business strategy. The research method used was qualitative descriptive with data collection through in-depth interviews with top management and employees/teams of 11 people consisting of various positions, as well as analysis of documents related to HR policies and programs. The results of the performance assessment conducted on 11 employees/teams showed that 45,45% of employee performance was very good, 27,27% of employee performance was good, and 18,18% of employee performance was at a moderate level. The data shows that the Rawramie startup has implemented several good MSDM practices. However, there is still a need for improvement in several aspects, especially in financial management and field monitoring.